Effects of Supplementation of Piper sarmentosum Leaf Powder on Feed Efficiency, Rumen Ecology and Rumen Protozoal Concentration in Thai Native Beef Cattle - Anusorn Cherdthong; Benjamad Khonkhaeng; Suban Foiklang; Metha Wanapat; Nirawan Gunun; Pongsatorn Gunun; Pin Chanjula; Sineenart Polyorach (My University, 2019)
Methane (CH4) is an end-product of enteric fermentation in cattle [...]
Keywords: Feed additive; Ruminant Nutrition and Digestive Physiology